Sterile Fluid Transfer for Cell Therapy Manufacturing—The Value of Multiple-Use Aseptic Connector - Wu, Ying Ying; Lee, Jia Sheng Zach; Chen, Sixun; Liu, Dan (Frontiers in Bioengineering and Biotechnology, 2022)
Sterile fluid transfer between vessels is a key step in cell therapy manufacturing and requires specialised devices to maintain sterility of both vessels before, during and after the transfer. This review introduces two main types of devices for sterile fluid transfer in cell therapy manufacturing, namely single-use sterile connectors and tube welders. While these are excellent devices for infrequent moderate to large volume transfers, a new multiple-use aseptic connector may fill the gap for frequent small volume fluid transfers that are particularly important for autologous cell therapy manufacturing.